Stradanje nesrpskog civilnog stanovništva na okupiranom području bivše općine Vukovar (1992.-1998.) - Ružić, Slaven (2020)
Autor je, na temelju izvornog arhivskog gradiva Republike Srpske Krajine, podataka Uprave za zatočene i nestale Ministarstva hrvatskih branitelja i Državnog odvjetništva Republike Hrvatske, kao i dostupne literature, pokušao ustanoviti broj stradalog (ubijenog) nesrpskog civilnog stanovništva okupirane vukovarske općine u razdoblju od siječnja 1992. do siječnja 1998. godine. Pritom se rukovodio činjenicom da je navedena tematika, neovisno o svojemu značaju, u suvremenoj hrvatskoj historiografiji gotovo posve zanemarena. Tekst, sukladno tome, valja smatrati tek uvodom u buduća, kompleksnija istraživanja problematike vezane uz izravne demografske gubitke domicilnog stanovništva na širem vukovarskom području za trajanja Domovinskog rata.
This text endeavours to determine the number of non-Serbian victims of the war in the occupied Vukovar Municipality in the period from the Sarajevo Peace Agreement on January 2, 1992 until January 15, 1998 when the Croatian Danube region became again a part of the constitutional legal order. The focal point is the manner and the circumstances of the sufferings of non-Serbian victims. The research was primarily based on archival source materials of the Republic of the Serbian Krajina which is kept in the Croatian Memorial Documentation Centre of the Homeland War in Zagreb with an emphasis on the files of the Vukovar Secretariat of the Interior from that period. Available data on the victims kept in the Administration of Detainees and Missing Persons of the Ministry of Croatian Veterans and of the State Attorney’s Office of the Republic of Croatia have also been consulted, as well available literature of both Croatian and Serbian provenance. In the territory of the (former) Vukovar Municipality, namely from 1992 to 1998 under insufficiently elucidated circumstances, a great number of Croatian civilians (as well as members of local national minorities, mainly Rusyns), who refused to go into exile and remained to live in their homes under the Serbian occupation, were killed. Compared to the events in this territory during 1991 in relation to the Battle of Vukovar, this topic is largely unexplored.
Bilješke uz tekst.
Bibliografske bilješke uz tekst.
Sažetak ; Summary.
Keywords: Domovinski rat -- Civilne žrtve -- Srpska okupacija; Vukovar -- Republika Srpska Krajina